The urban dimension in the EU cohesion policy in Germany. EU funding period 2014-2020. - (:unkn) unknown (My University, 2020)
The study points out the positive effects that Structural Funds produce for the integrated urban development in large, medium-sized and small cities and communities in Germany. The funds are used for upgrading deprived neighbourhoods, mobility and climate protection, education and training or intermunicipal as well as interregional development strategies. The Structural Funds constitute together with the Operational Programmes at national and Länder level an effective instrument for strengthening integrated urban development. The principal investigators of this research project analysed the approval and flow of the programme’s funds, interviewed responsible decision-takers on the Länder level and in projects and screened case studies in cities and communities of different sizes.
Keywords: Europäische Zusammenarbeit; Strukturpolitik; Strukturfonds; Förderprogramm; Wirkungsanalyse; Integrierte Stadtentwicklung; EU-Kohäsionspolitik; EU-Förderung